Enhancing Graduate Competitiveness Through Competency Assessor Training: Implications for Certification System Development - Jajang Ikbal Herlianto; Yayah Rahyasih (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the influence of competency assessor training on the development of a certification system and the enhancement of graduate competitiveness at the Professional Certification Body (LSP) P1 SMKN 1 Ciamis. Strengthening assessor capacity is essential to ensure objective, credible assessments that align vocational graduates’ skills with industry demands. A descriptive quantitative design was used, involving a saturated sample of 30 competency assessors. Data were collected through a validated and reliable questionnaire (Cronbach’s Alpha = 0.957), measuring perceptions related to training effectiveness and graduate competitiveness. Data analysis employed descriptive statistics, Pearson correlation, and regression analysis using SPSS. Findings revealed strong, statistically significant correlations between the quality of assessor training and both the alignment of certification standards with industry needs (r = 0.793, p 0.05) and the improvement in graduate competency test outcomes (r = 0.819, p 0.05). The regression model confirmed that key training variables significantly predicted graduates’ competitive advantage (Sig. 0.001). Results confirm that well-designed assessor training programs contribute directly to strengthening certification quality and enhancing graduates’ job readiness. These findings support the need for sustained investment in training to ensure reliable certification outcomes that meet labor market expectations. Competency assessor training plays a critical role in improving vocational certification systems and graduate competitiveness. The study provides empirical evidence for policymakers and educational institutions to enhance training strategies and workforce alignment.